Rancang Bangun Aplikasi Chatting Berbasis Mobile Menggunakan React Natice - Sabdho Cathur Kuncoro; Sewaka (CV. Multi Kreasi Media, 2022)
The development of information technology has had a very rapid impact on the development of daily human activities. With the development of today's technology, humans can easily communicate remotely with each other anytime and anywhere. In this case the application with a chat service is one of the media for communication that is widely used by the community. In making this application, the framework used to build the frontend view is React Native, and the backend uses Firebase. The coding process is done using Visual Studio Code. The method used in making this chat application uses the waterfall method. This application can be used to exchange messages personally between users and also between users in a group. This application can be used to send messages in the form of text or in the form of images. The results of tests carried out using a Likert scale, obtained an average total percentage of 89% of users stating that this mobile-based chat application can be used as an alternative medium in exchanging messages.